Pengaruh Model PjBL-STEM Terhadap Keterampilan Berpikir Kritis Pada Materi Analisis Transaksi - Ihsan, Ihsan; Yaqutunnafis, Lale (Universitas Hamzanwadi, 2024)
The habit of applying conventional learning models in the learning process causes students' thinking power and critical thinking skills to be less developed. This research is aimed at comparative analysis of the influence of the PjBL based STEM learning model with discussion in significantly improving students' critical thinking skills. The research used a quasi-experimental design, pretest-posttest non-equivalent control group design. The research subjects were taken using a cluster random sampling technique totaling 40 students who were divided into two different classes. Data was collected using cognitive tests in the form of financial transaction story questions. Data analysis used normalized N-Gain score and two mean difference test assisted by SPSS IBM Vers. 25. The research results prove that the PjBL based STEM learning model has a significant effect on improving students' critical thinking skills by achieving a normalized N-gain score of 0.75, a high criterion. Meanwhile, the discussion method is in the medium criteria with a normalized N-gain score of 0.58. In addition, the PjBL based STEM model is applied to create varied learning nuances, individual mental formation, responsibility, including improving analytical and critical thinking skills